A New Variable for Tunnel Blast Efficiency: the Angles of Breakage of Explosive Charges - Seccatore, Jacopo; Cardu, Marilena; Marin, Tatiane; Golin, Fernando (Archives of Mining Sciences, 2026)
Tunnel excavation by drill and blast requires creating an effective opening cut to provide a free surface for subsequent rock breakage. While numerous studies have examined blast design parameters, the exact shape and dimensions of the rock volume assigned to each blasthole have yet to be recognised as critical variables. This study introduces the angle of breakage as a measurable parameter and evaluates its influence on tunnel advance efficiency in blast rounds with parallel-hole cuts. More than 60 tunnel blast designs, as recorded in the Atlas of Blasting Rounds for Tunnel Driving, were analysed. The angles of breakage were determined from blast layouts by using CAD tools and following the delay sequence. Only holes with defined initiation timing were considered. Contour holes and simultaneous delays were excluded. For each blast, the average angle of breakage was calculated and correlated with advance efficiency, defined as the ratio between actual pull (PR) and designed pull (PD). Measured angles ranged from 35° to 140°, with typical industrial averages above 50°. The results show a clear inverse relationship between the average angle of breakage and advance efficiency. A threshold behaviour was identified at approximately 60°, above which efficiency decreases systematically. The highest efficiencies were observed for average angles near 65°. Statistical analysis indicates that the angle of breakage presents a stronger correlation with efficiency (R² up to 0.67 for homogeneous lithological sets) than conventional design parameters such as burden, spacing, powder factor, or hole diameter. Three lithological clusters were identified. A heterogeneous set shows scattered behaviour. A second set, representing the majority of cases across mixed lithologies, exhibits a consistent inverse trend. A third set, composed mainly of competent intrusive igneous rocks, displays a more defined correlation between increasing angle and decreasing efficiency. These results indicate that lithology modulates the sensitivity of efficiency to geometric design parameters. The findings demonstrate that the angle of breakage is a relevant design variable for tunnel blasting. Increasing the angular width of the rock prism assigned to each blasthole increases resistance to breakage and reduces advance efficiency. Blast designs based on narrower angles of breakage provide more favorable conditions for rock fragmentation and displacement. The results support the inclusion of this parameter in blast design methodologies and in the interpretation of tunnel excavation performance.